2019
DOI: 10.3390/jcm8122189
|View full text |Cite
|
Sign up to set email alerts
|

Management of Immunosuppression in Kidney Transplant Recipients Who Develop Malignancy

Abstract: The risk of cancer increases after transplantation. However, the consensus on immunosuppression (IS) adjustment after diagnosis of malignancy is lacking. Our study aims to assess the impact of IS adjustment on mortality of post-kidney transplant patients and allograft outcomes. We retrospectively reviewed the data in our center of 110 subjects. Our results showed IS dose adjustment was not statistically associated with mortality risk (HR 1.94, 95%CI 0.85–4.41, p = 0.12), and chemotherapy was the only factor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In these scenarios, 58% to 67%, depending on the specific query, of the panel preferred to defer this decision to transplant physicians. Although the absence of such a recommendation runs contrary to previous expert statements and some RCTs have demonstrated that reduction of immunosuppression or conversion to mTOR-based immunosuppression may decrease CSCC formation, this discrepancy is instructive regarding the balance expert physicians must use in management of SOTRs: patients with reduced immunosuppression are at risk for inferior graft survival, and conversion to mTOR may affect overall survival …”
Section: Discussionmentioning
confidence: 86%
“…In these scenarios, 58% to 67%, depending on the specific query, of the panel preferred to defer this decision to transplant physicians. Although the absence of such a recommendation runs contrary to previous expert statements and some RCTs have demonstrated that reduction of immunosuppression or conversion to mTOR-based immunosuppression may decrease CSCC formation, this discrepancy is instructive regarding the balance expert physicians must use in management of SOTRs: patients with reduced immunosuppression are at risk for inferior graft survival, and conversion to mTOR may affect overall survival …”
Section: Discussionmentioning
confidence: 86%
“…There are no systematic reviews or RCTs on this topic. Only two small ( n = 87 and n = 110), retrospective cohort studies were identified [ 7 , 8 ] comparing outcomes in KTRs with post‐transplant cancer between those remaining on standard immunosuppression and those who underwent reduction of immunosuppression. However, no clear conclusions could be drawn from these studies because of the low number of patients, high heterogeneity of cancer types and cancer stages, varying immunosuppressive regimens and a high risk of indication bias, because the patients who were switched to a reduced immunosuppressive regimen are more likely to be those with an inferior prognosis (Table S1 ).…”
Section: Results Of the Systematic Literature Searchmentioning
confidence: 99%
“…There are no systematic reviews or RCTs on this topic. Only two small (n = 87 and n = 110), retrospective cohort studies were identified [7,8] who were switched to a reduced immunosuppressive regimen are more likely to be those with an inferior prognosis (Table S1). A second literature search, specifically on PTLD, yielded no studies matching our inclusion criteria (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, no strategies have proven effective without unacceptable impacts on transplanted organs and/or the patients themselves. For example, reducing the dose of immunosuppressive medications can decrease malignancy rates, however, such approaches have been linked to an increased risk of graft failure 16 and an increased frequency of transplant rejection. 17 Alternatively, switching from a calcineurin inhibitor-based treatment regime to a mammalian target of rapamycin (mTOR) inhibitor-based treatment regimen can reduce de novo SCC formation [18][19][20][21] and induce the regression of pre-existing premalignant lesions.…”
Section: What This Study Addsmentioning
confidence: 99%